Environmental impact of rural-urban migration in the federal capital territory Abuja, Nigeria - Medugu, Nasiru Idris (2014)
The impact of population growth and housing development in developing countries is usually a consequence of the push of the rural areas and the pull of the town. The growth and physical expansion of cities have been accompanied by unplanned urban sprawl, environmental pollution, deterioration, deficiencies in modern basic facilities, and general urban decay. Urban expansion without effective environmental consciousness means that in virtually every urban center – from large cities and metropolitan areas to regional centers and small market towns – a substantial proportion of the population is at risk from natural and human-induced environmental hazards. A strategic approach is essential if urban areas are to enjoy all the benefits which nature can bring. A total of 200 copies of questionnaires were administered at the neighbourhood zones I, II, III and IV of peri-urban Nyanya town for the purpose of assessing the impact of urbanization towards the suburb in other to ascertain its general environmental condition on the surrounding landscape. The study examines the environmental consequences of socioeconomic and other activities in a bid to determine how sustainable Abuja’s urbanization is. The study reveals that, the city is growing faster than in the provisions of its master plan. It is fast turning into an environmental embarrassment, with developments springing up in gross violation of zoning and other planning codes. Abuja, which was supposed to be an epitome of beauty and an enlightened vision of city development, has suffered over the years from unnecessary distortions in the implementation of its master plan. The paper concludes by suggesting pragmatic strategies for achieving an integrated and ecologically balanced environment. Therefore, this paper recommends the review of the Abuja master plan for every five years to reflect the garden city concept and neighbourhood design for sustainable city living and mitigating the serious negative impacts of urbanization